Concentración de metales pesados en jaiba azul (Callinectes arcuatus) del refugio de vida silvestre “Isla Corazón”, cantón Sucre- Manabí - Ramírez Espinoza, Nathalie (2022)
The objective of this research was to determine the concentrations of heavy metals (Hg, Pb and Cd) in the hepatopancreas of the blue crab (Callinectes arcuatus) of the "Isla Corazón" wildlife refuge as an indicator of anthropogenic contamination surrounding the area such as: shrimp farms, agriculture and human settlement. For the evaluation of concentrations of heavy metals (Hg, Pb and Cd) in the hepatopancreas of the blue crab (Callinectes arcuatus) the following techniques were used: ICP-OES (Inductive Coupled Plasma) and the EPA 3015ª and EPA 3051 methods in the laboratory. from the University of the Americas (UDLA). An analysis of variance, Tukey's test of significance and Pearson's correlation coefficient were applied between the concentrations of (Hg, Pb and Cd) and the physicochemical parameters of water and sediment. According to the data obtained in the months of May, July and August, the results of mercury with concentrations between 0.001 mg/kg and 0.170 mg/kg were shown, which are within the permissible limit, while the concentration of lead is from 0.269 mg/kg to 2,542 mg/kg and cadmium from 0.430 mg/kg to 17,137 mg/kg, showing that they exceeded the limits established by the European Food Safety Authority (EFSA, 2015). The statistical analyzes of the physical-chemical parameters of water and sediment with the concentrations of the metals Hg and Pb did not show a significant difference because the values of (p) are greater than 0.05. However, the sediment temperature and the Cd concentration did present a significant difference with a strong correlation.